Prediktor Left Main DiseasePada Pasien NSTEMI Akut Berdasarkan Elektrokardiogram - Budiyanto Nagawidjaja; Hadi Purnomo; Budhi Setianto (Jurnal Kardiologi Indonesia, 2007)
Background. The importance to identify Left Main (LM) disease in Coro-nary Artery Disease (CAD) patients is to define therapy strategy, progno-sis which can influence to length of hospitalization, survival rate, and the payment. Electrocardiogram (ECG) is a simple tool to diagnose patient with CAD.Objectives. To identify ECG indicators as related to LM disease predic-tors.Methods. 265 acute non ST elevation patients enrolled after having coro-nary angiography in National Cardiovascular Center Harapan Kita Jakarta. ST elevation, ST depression, T invertion of the 12 lead ECG and ST eleva-tion in aVR taller than V1 lead is further variable investigation. Chi-square and Mann-Withney test were done for statistical analysis. Logistic regres-sion was used in variable predictor test. Discrimination test was done by using Hosmer Lemeshow goodness of fit to determine validation model and area under curve test.Results. The largest populations were male (210 patients – 82.3%). The age range from 37 until 80 years old (mean 59,9 ± 9,1 years), 77 patients were more than 65 years old. There were 90 patients with LM disease. There was ST elevation in aVR in 88 patients, and 87 patients had higher ST elevation compared to ST segment in V1. The significant factors areelevation of ST segment in aVR, ST segment elevation in aVR > V1, ST depression in I, II, III, aVL, aVF, V2 - V6, ST elevation in lead aVR–V1, mul-tiple ST changes (elevation and depression) in many leads. Multivariate analysis showed the highest parameter to diagnose LM disease are ST el-evation in aVR and ST elevation aVR-V1 (mm) with area under curve 96% (sensitivity 92,22 / specificity 97,14 / PPV 94,31 / NPV 96,00 for ST eleva-tion in aVR and sensitivity 93,33 / specificity 98,29 / PPV 96,55 / NPV 96,62 for ST elevation aVR>V1).Conclusions. ECG indicators for LM disease are ST elevation in aVR and ST elevation in aVR>V1.